A randomized controlled trial of coenzyme Q10 for fatigue in the late-onset sequelae of poliomyelitis. Issue 6 (December 2015) - Peel, Margaret M.; Cooke, Marie; Lewis-Peel, Helen J.; Lea, Rodney A.; Moyle, Wendy
Highlights: Alleviation of fatigue in late-onset sequelae of poliomyelitis was investigated. A placebo-controlled trial compared fatigue levels after coenzyme Q10 dosage. Daily intake of 100 mg coenzyme Q10 for 60 days did not significantly reduce fatigue. Suggest that coenzyme Q10 at increased dosage be tested for relief of the fatigue. Abstract: Objective: To determine if coenzyme Q10 alleviates fatigue in the late-onset sequelae of poliomyelitis. Design: Parallel-group, randomized, placebo-controlled trial. Background setting: Coenzyme Q10 has been shown to boost muscle energy metabolism in post-polio subjects but it does not promote muscle strength, endurance or function in polio survivors with post-poliomyelitis syndrome. However, the collective increased energy metabolism might contribute to a reduction in post-polio fatigue. Participants: Polio survivors from the Australian post-polio networks in Queensland and New South Wales who attribute a moderate to high level of fatigue to their diagnosed late-onset sequelae of poliomyelitis. Those with fatigue-associated comorbidities of diabetes, anaemia, hypothyroidism and fibromyalgia were excluded. Method: Participants were assigned (1:1), with stratification of those who use energy-saving mobility aids, to receive 100 mg coenzyme Q10 or matching placebo daily for 60 days. Participants and investigators were blinded to group allocation. Fatigue was assessed by the Multidimensional Assessment of Fatigue as the primary outcome and the Fatigue Severity Scale as secondary outcome. Results: Of 103 participants, 54 were assigned to receive coenzyme Q10 and 49 to receive the placebo. The difference in the mean score reductions between the two groups was not statistically significant for either fatigue measure. Oral supplementation with coenzyme Q10 was safe and well-tolerated. Conclusion: A daily dose of 100 mg coenzyme Q10 for 60 days does not alleviate the fatigue of the late-onset sequelae of poliomyelitis. The registration number for the clinical trial is ACTRN 12612000552886.